27.4k views
1 vote
Helppppp plsssss!!!!!

Helppppp plsssss!!!!!-example-1
User Xnx
by
5.7k points

1 Answer

4 votes

X^2 + 2x -4= 0

You need to remember one standard result

ax^2 + bx + c= 0


x = \frac{ - b + - \sqrt{ {b}^(2) - 4ac} }{2a}

By Comparing the coefficients,

a= 1, b=2, c=-4


x = \frac{ - 2 + - \sqrt{ {2}^(2) - 4 * 1 * - 4 } }{2 * 1} \\ x = ( - 2 + - √(4 + 16) )/(2) \\ \\ x = ( - 2 + - √(20) )/(2) \\ \\ x = ( - 2 + - 2 √(5) )/(2) \\ \\ x = - 1 + - √(5)

Options A ,C

User Quincey
by
6.6k points